2018
DOI: 10.1016/j.matdes.2018.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Defect-free TiC/Si multi-layer electrical discharge coatings

Abstract: The process of electrical discharge coating (EDC) may be used to deposit hard materials on conformal substrate surfaces. Next generation EDM'd components may exploit attachment phenomena to enhance recast layer properties, to avoid the need for recast layer removal. Here, a ceramic based composite layer was developed without cracking and porosity for the first time, using sequential coating using sacrificial TiC and Si electrodes. Attenuation of the discharge process by gap widening using Si debris in the gap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 28 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…This method consists of alternatives in the rows and attributes in the columns. The matrix format can be expressed as follows [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method consists of alternatives in the rows and attributes in the columns. The matrix format can be expressed as follows [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. …”
Section: Methodsmentioning
confidence: 99%
“…It was observed that WS2 increases coating thickness whereas current and duty factors influence wear and hardness. Murray et al [ 22 ] reported their work varying the input parameters of EDC to coat different materials of copper, zirconium and tungsten carbide on stainless steel. Bui et al [ 23 ] studied the elemental composition of the modified workpiece surface, tool electrode and dielectric fluid with immersed powder particles.…”
Section: Introductionmentioning
confidence: 99%
“…This voltage difference created a dielectric breakdown and, because of this spark, it was generated between the electrode surface and the part closest to the substrate surface, which generates heat and it melts the loosely compacted electrode surface particles. After melting, the molten particles move towards the substrate because of the electromotive force generated and the applied voltage, and these particles get settled down in the substrate surface and make uniform coating layer by layer [18,19] if suitable process parameters are used. Overall, this process takes place periodically and continuously for a specified amount of time and this leads to a layer-by-layer coating process and its thickness depends on the time of the coating process and other parameters.…”
Section: Introductionmentioning
confidence: 99%
“…μEDC is one such method that can figure out the problems associated with micro-parts for localized coating and/or alloying by surface modification methods. The process is carried out in different ways, such as the formation of a modified recast layer during the material removal process [12], altering the dielectric fluid by adding powders [13], using green compact tool electrode [14], and by using brush electrodes [15]. The surface modification using powder metallurgy tool and powders mixed in the dielectric fluid is frequently used over other methods.…”
Section: Introductionmentioning
confidence: 99%